2013
DOI: 10.1002/micr.22207
|View full text |Cite
|
Sign up to set email alerts
|

Functional and electrophysiological outcome after autogenous vein wrapping of primary repaired ulnar nerves

Abstract: Vein wrapping is a simple technique that could be used reliably to augment primary neurorrhaphy particularly in cases with associated vascular or tendon injuries to prevent scarring and enhance functional and electrophysiological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Several clinical studies have demonstrated promising results, including the reduction of allodynia, using the vein wrapping technique for the treatment of recurrent compressive neuropathy and traumatic peripheral nerve injury. [3][4][5][6][7][8][9][10] Previous experiments by our group in a rat model revealed that vein wrapping after CCI decreased pain-associated behavior and nerve damage. 34 Here, vein wrapping also inhibited the development of allodynia following CCI.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Several clinical studies have demonstrated promising results, including the reduction of allodynia, using the vein wrapping technique for the treatment of recurrent compressive neuropathy and traumatic peripheral nerve injury. [3][4][5][6][7][8][9][10] Previous experiments by our group in a rat model revealed that vein wrapping after CCI decreased pain-associated behavior and nerve damage. 34 Here, vein wrapping also inhibited the development of allodynia following CCI.…”
Section: Discussionmentioning
confidence: 86%
“…The technique of using autologous veins as a protective material is called “vein wrapping.” Masear et al first reported the successful use of vein wrapping for reducing recurrent symptoms secondary to nerve scarring. Several basic and clinical studies have shown that in patients with recurrent compressive neuropathy, such as carpal tunnel, cubital tunnel, radial tunnel, and tarsal tunnel syndromes, and traumatic peripheral nerve injury, vein wrapping improves nerve function and the symptoms associated with these disorders . However, despite the therapeutic potential of autologous vein wrapping, the underlying mechanisms of this technique have not been resolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous vein wrapping has improved treatment for neuropathic pain resulting from recurrent compressive neuropathy and traumatic peripheral nerve injury . Vein wrapping has been used to improve recurrent symptoms arising from nerve scarring since the early 1990s .…”
mentioning
confidence: 99%
“…To overcome this problem, collagen materials have recently been developed as an alternative to autologous veins . Vein wrapping was first employed in the upper extremity to avoid scarring in peripheral nerve injury . Realization that vein tissue produced several trophic factors that play an important role in the relief of pain was another important milestone .…”
mentioning
confidence: 99%